2013
DOI: 10.1177/0300060513476590
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between arterial stiffness and variability in systolic blood pressure during a single clinic visit in patients with hypertension

Abstract: Objective: To examine factors affecting systolic blood pressure (SBP) variability during a single clinic visit, in treated hypertensive patients. Methods: Hypertensive patients were recruited to this observational study. Blood pressure was measured using an automated blood pressure monitor when each patient arrived at the outpatient clinic and again when they saw the physician. Mean SBP and SBP variability during a single clinic visit were calculated. The cardio-ankle vascular index (CAVI), as a marker of arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Our findings of general associations between BP variability and arterial stiffness in young people extend findings from older populations. Schillaci et al [ 18 ] showed BP variability correlated with carotid–femoral PWV in an older hypertensive population (mean age 49 ± 11 years), and Masugata et al [ 37 ] demonstrated similar associations in a cohort 20 years older using CAVI to assess arterial stiffness ( r = 0.33, P = 0.01).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings of general associations between BP variability and arterial stiffness in young people extend findings from older populations. Schillaci et al [ 18 ] showed BP variability correlated with carotid–femoral PWV in an older hypertensive population (mean age 49 ± 11 years), and Masugata et al [ 37 ] demonstrated similar associations in a cohort 20 years older using CAVI to assess arterial stiffness ( r = 0.33, P = 0.01).…”
Section: Discussionmentioning
confidence: 94%
“…Some cardiovascular risk factors such as age, hypertension, and obesity have been confirmed to be positively correlated with arterial stiffness [2,3]. As a well-established anti-risk factor, the cardioprotective effects of HDL cholesterol (HDL-C) have been documented by clinical and experimental research [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Masugata et al reported that variability in SBP (differences between the SBPs of the two measurements within a single visit) within a single clinic visit showed better correlations with arterial stiffness and risk factors for atherosclerosis than the mean SBP. Large SBP variability during a single clinic visit may reflect the progression of atherosclerosis in treated hypertensive patients [ 31 ]. Beat-to-beat BPV was associated with aortic stiffness and aortic pulsatility [ 32 ].…”
Section: Discussionmentioning
confidence: 99%